Impact of agricultural and tillage systems on the main pests of winter wheat - S. Tanchyk; O. Pavlov; A. Babenko (Рослинництво та ґрунтознавство, 2021)
The intensification of agriculture has some adverse consequences, and the preservation of land resources during their active exploitation is a vital issue today, given the ever-increasing need to increase food supply. The world practice of organic farming shows limited regulation of the number of pests of agricultural crops. Artificially increasing natural enemies and altering the landscape to enhance biological control is not a popular solution and has controversial effectiveness. The number of winter wheat entomocomplex was monitored according to generally accepted methods on 48 plots, where 12 variants were placed in 4 repetitions during 2019-2021. This paper presents the results of a study indicating a substantial impact of agricultural systems on the main pests of winter wheat and the ability to control their numbers according to the ecological system at the level of the economic threshold of harmfulness. Tillage variants did not regulate the number of Schizaphis graminum R., Eurygaster integriceps R. and Oulema melanopus L., while chisel tillage at 20-22 cm regulated the number of Anisoplia austriaca N. and Haplothrips tritici Kurd at the level of the control (ploughing) in all years of observations. In the case of surface cultivation of the soil to a depth of 6-8 cm, the number of these pests increased substantially, and was on average at 2.0 and 14.4 specimens/m2, respectively. Thus, the highlighted data confirm the effectiveness of reducing the multiplicity of insecticidal treatments of winter wheat in the ecological system without increasing the risks of crop loss due to pest damage to plants in combination with chisel tillage